High-pressure electrorheological valve with full pQ-functionality for servohydraulic applications. (September 2015) - Heinken, Helge; Krivenkov, Konstantin; Ulrich, Stephan; Bruns, Rainer
Stationary and mobile hydraulic systems require switching increasing velocity, power and efficiency. Usually, their performance mainly faces physical constraints by the valves. These are in particular electrical and magnetic losses as well as various flow saturation effects. Compared to conventional valves, some of these physical constraints do not appear in electrorheological valves. However, electrorheological valves being employed as valves in conventional hydraulic systems were previously unimaginable due to the small controllable pressure differences. The presented new kind of electrorheological valve obtains a significant performance enhancement by combining the potential of conventional and electrorheological systems.